Nephroprotective effects of Helianthus annuus seeds extract in gentamicin induced nephrotoxic male mice - Ali, Arif; Khan, Haroon; Kahrizi, Danial; Pervez, Samreen; Alotaibi, Ghallab; Rastrelli, Luca (Cellular and Molecular Biology, 2022)
Acute kidney injury (AKI) causes a decrease in renal function which leads to failure in balancing electrolyte, fluid and acid-base homoeostasis. AKI is a damaging and life-threatening disorder, but it can be managed if identified earlier. This study aimed to investigate the possible nephroprotective effect of Helianthus annuus seeds extract against gentamicin (GM) induced nephrotoxicity in male mice. The control group (0.5 ml normal saline i.p.,), Gentamycin (GM) group (GM 100 mg/kg i.p), silymarin + GM group (silymarin 50 mg/kg and GM 100 mg/kg i.p.,), H. annuus extract (HAE) and GM, group (HAE 250 mg/kg and GM 100 mg/kg i.p), HAE2 + GM group (HAE2; 500 mg/kg and GM 100 mg/kg i.p) and H. annuus oil (HAO) + GM (HAO 2.5 ml/kg and GM 100 mg/kg i.p). Serum creatinine, urea and blood urea nitrogen (BUN) were significantly (P< 0.001) elevated in the GM group compared to the control group. The elevated level of serum creatinine, urea and BUN were decreased significantly (P<0.001) in groups treated with HAE and HAO extracts compared to the GM group. The kidney histopathological study from the GM group showed tubular necrosis, vacuolation and fibrosis. However, the animal that received HAE and HAO showed no tubular necrosis and vacuolation. Only mild inflammation was observed compared to the GM group. In conclusion, the extract caused marked radical scavenger and protected the kidney from oxidative damage of GM. H. annuus seeds contain strong antioxidant compounds, including flavonoids, phenolic acids, tocopherols and minerals, which could be responsible for the current show.